Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Penghindaran Pajak: Pada Perusahaan Manufaktur Sektor Kesehatan Yang Terdaftar di Bursa Efek Indonesia 2019-2023 - Emira, Mustika Balqis; Pertiwi, Indah (Prisani Cendekia, 2025)
This study aims to analyze the effect of capital intensity, leverage, and firm size on tax avoidance in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. A quantitative approach was employed using panel data regression to examine the relationships among variables. The findings indicate that capital intensity has a significant negative effect on tax avoidance, suggesting that investment in fixed assets tends to reduce tax avoidance practices. Leverage shows no significant effect, meaning that financing structure through debt does not directly influence tax avoidance strategies. Firm size is found to have a significant positive effect, indicating that larger-scale companies tend to have a higher propensity for tax avoidance. These findings contribute to the development of the tax management literature and serve as a reference for regulators in formulating more effective tax oversight policies.